The Biology of Polymorphic Melanic Side-Spotting Patterns in Poeciliid Fishes - Zerulla, Tanja C.; Stoddard, Philip K. (Frontiers in Ecology and Evolution, 2021)
Melanin-based color patterns are an emerging model for studying molecular and evolutionary mechanisms driving phenotypic correlations. Extensive literature exists on color patterns and their correlated traits in the family Poeciliidae, indicating that these fishes are tractable models. We review the biology of polymorphic melanic side-spotting patterns characterized by macromelanophores forming irregular spotted patterns across fishes’ flanks. These patterns are present in the genera Gambusia, Limia, Phalloceros, Poecilia, and Xiphophorus. Their presence is controlled by dominant genes on autosomes or sex chromosomes. Variation in expression is under polygenic control; however, these genes’ identities are still largely unknown. In some Gambusia holbrooki and Poecilia latipinna, expression is dependent on low temperature exposure, but underlying molecular mechanisms are unknown. Spotted fish develop melanoma in rare cases and are a well-developed model for melanoma research. Little is known about other physiological correlates except that spotted G. holbrooki males exhibit higher basal cortisol levels than unspotted males and that metabolic rate does not differ between morphs in some Xiphophorus species. Behavioral differences between morphs are widespread, but specific to population, species, and social context. Spotted G. holbrooki males appear to be more social and more dominant. Juvenile spotted G. holbrooki have lower behavioral flexibility, and spotted X. variatus exhibit greater stress resistance. Findings conflict on whether morphs differ in sexual behavior and in sexual selection by females. Melanic side-spotting patterns are uncommon (<30%) in populations, although extreme high-frequency populations exist. This low frequency is surprising for dominant genes, indicating that a variety of selective pressures influence both these patterns and their correlated traits. Little is known about reproductive life history traits. Spotted G. holbrooki are larger and have higher survival when uncommon, but underlying mechanisms remain unknown. Spotted morphs appear to have a strong selective advantage during predation. Predators prefer to attack and consume unspotted morphs; however, this preference disappears when spotted G. holbrooki males are common, indicating negative frequency-dependent selection. Spotted morphs are preferred socially under turbid conditions, but other environmental factors that shape phenotypic correlations and morph fitness have not been studied. Finally, we present questions for future studies on melanic side-spotting patterns.